The impact of surfing on tourism in Portugal - Martins, Salvador do Canto Moniz (2022)
The Sea, (O Mar) has always been an essential part of the Portuguese National Identity. Surfing is an emerging global trend and a brand image. Over the past decades, the Economy of the Sea has gained an increasing importance and the “Return to the Sea" has actively promoted surf as one of its most significant activities. The current study provides a descriptive and analytic research on the importance of the Sea and the impact of Surf on Tourism in Portugal. In particular, it examines the surf industry, its potential and contribution to tourism as well as its effect on local economy with a particular focus on of Ericeira - the only World Surf Reserve in Europe. Results demonstrate how a change in social perspective contributes to the growth of surfing, impacting the professionalization within the sector and hosting of international surfing events. As implied, Portugal can maintain its position as Europe’s preferred surfing destination due to the country’s quality of natural resources and international promoting campaigns. Results illustrate how surfing has enhanced tourism, as seen through both the consistent increase of tourists in Ericeira and number of local businesses. Whilst this sector is not fully exploited, the need to; protect natural resources, create legal frameworks and the preserve the people’s identity, is kept in mind. There is definitely positive development in Ericeira and surf, as a mean of opening up mentalities, projecting Portugal as a touristic destination, its image as a modern country with new mentalities, where differences are accepted.